Legal advice privilege and artificial legal intelligence: Can robots give privileged legal advice?. (October 2019) - Stockdale, Michael; Mitchell, Rebecca
Legal professional privilege entitles parties to legal proceedings to object to disclosing communications. The form of legal professional privilege that is now commonly known as 'legal advice privilege' attaches to communications between a client and its lawyers in connection with the provision of legal advice. The provision of legal advice increasingly involves the use of technology across a wide spectrum of activities with varying degrees of human interaction or supervision. Use of technology ranges from a lawyer conducting a keyword search of a legal database to legal advice given online by fully automated systems. With technology becoming more integrated into legal practice, an important issue that has not been explored is whether legal advice privilege attaches to communications between client and legal services provider regardless of the degree of human involvement and even if the 'lawyer' might constitute a fully automated advice algorithm. In essence, our central research question is: If a robot gives legal advice, is that advice privileged? This article makes an original and distinctive contribution to discourse in this area through offering novel perspectives on and solutions to a question which has not previously been investigated by legal academics.